All or Nothing: State Capacity and Optimal Public Goods Provision - Felix Bierbrauer; Justus Winkelmann (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study the provision of public goods. Different public goods can be bundled provided there is enough capacity, i.e. resources to pay for all the public goods in the bundle. The analysis focuses on the all-or-nothing-mechanism: Expand provision as much as resource feasible if no one vetoes - otherwise stick to the status quo. We show that the probability of the all-outcome converges to one as the capacity becomes unbounded. We also provide conditions under which the all-or-nothing-mechanism is ex ante welfare-maximizing - even though, ex post, it involves an overprovision of public goods.
Keywords: D79; D82; H41; 330; public goods; bundling; state capacity; mechanism design